Proposed new interior design of child care centre at No 3 and No 5 Lorong IM10/16, Bukit Istana Kuantan for TASKA Tok Sira / Nur Qamarina Mohd Ali - Mohd Ali, Nur Qamarina (Faculty of Architecture, Planning and Surveying, 2012)
Final student of Diploma Interior Architecture needs to do final report to fulfill one of the requirements in order to graduate, come out with a project report in order to understand the whole final project in every aspects. The final project is Proposed New Interior Design of Child Care and Learning Centre At No 3 and No 5 Lorong IM10/16, Bukit Istana, Bandar Indera Mahkota, 25200 Kuantan for PuanSamsiah Bt Dato’ Abu BaKar. Child Care and Learning Centre is a place for children from 1 month until 6years old. It is a place for infant care and learning place for children below 7years old. The client of this project is Puan Samsiah Bt Dato’ Abu Bakar. She is the owner of Taska and Tadika Tok Sira. Puan Samsiah would like to combine her Taska and Tadika under <?ne roof so it would be easier for her to supervise each of the children. During my visit to the client’s place, I found that there are l<?ts of design problems which is dangerous and not suitable for the children. The client would like to have a new look with new safety furniture provided to her place as the place involved children. This project is being proposed according to the client’s requirement. The project is to create a spatial design complete with facilities for infant and children for their state of ease and contetnment . Apart from that, it will be design with \\ie highest possible level of safety in mind and provides opportunities for sensory, cognitive, creative, social and emotional stimulation during the child’s crucial growing development. The main objective is to design a Child Care and Learning Centre that combine both Taska and Tadika Tok Sira as requested by the client. The process of compliting this project is held according to the design stage, start with project brief, research and analysis, case study and lastly design proposal. To conclude, this project is a new interior design scheme which need to do lots of research on child care and learning centre as a place like this is rarely seen in Malaysia.